2003
DOI: 10.1677/jme.0.0310359
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin type 2 receptor of angiotensin II and neuronal differentiation: from observations to mechanisms

Abstract: The angiotensin II (Ang II) type 2 receptor (AT 2 ) is a member of the seven-transmembrane domain, G-protein coupled receptor family. This receptor is ubiquitously distributed in the fetus but, in most tissues, its expression dramatically falls in the first few hours after birth. Based on this observation, the hypothesis that this receptor could be involved in fetal development was raised and, over the past ten years, many studies have tried to identify a role for the AT 2 receptor using many different tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 113 publications
4
89
0
2
Order By: Relevance
“…Our preliminary results indicate that AT 2 stimulates cell process formation in UB cells in vitro [33]. This observation is consistent with the ability of AT 2 to induce neurite outgrowth and elongation [75]. The ultimate effect of ANG II on UB branching may depend on the balance between AT 1 -and AT 2 -mediated actions, cellular context, temporal profiles of the local concentrations of ANG II in specific spatial microdomains or the ability to establish a concentration gradient during critical periods of branching morphogenesis.…”
Section: Mechanisms Of Ang Ii-dependent Ub Branching Morphogenesis Ansupporting
confidence: 87%
“…Our preliminary results indicate that AT 2 stimulates cell process formation in UB cells in vitro [33]. This observation is consistent with the ability of AT 2 to induce neurite outgrowth and elongation [75]. The ultimate effect of ANG II on UB branching may depend on the balance between AT 1 -and AT 2 -mediated actions, cellular context, temporal profiles of the local concentrations of ANG II in specific spatial microdomains or the ability to establish a concentration gradient during critical periods of branching morphogenesis.…”
Section: Mechanisms Of Ang Ii-dependent Ub Branching Morphogenesis Ansupporting
confidence: 87%
“…While AT 2 R expression is low in several adult tissues, there is a general consensus that AT 2 R promotes vasodilatation, growth inhibition, cell differentiation and apoptosis (de Gasparo et al 2000, St-Louis et al 2001, Gendron et al 2003. However, in the adrenal ZG, AT 2 R expression is maintained at a high level, even in the adult (Breault et al 1996, Frei et al 2001.…”
Section: Adrenal Changes Induced By Nacl Supplementationmentioning
confidence: 99%
“…Furthermore, in addition to the humoral RAS, all components of the RAS exist in many tissues (Ganong, 1994;Re, 2004). The brain possesses a local angiotensin system (Gendron et al, 2003;McKinley et al, 2003;Pan, 2004;Rodriguez-Pallares et al, 2004), and the results of previous studies have suggested that AII and its receptors play an important role in modulating striatal dopamine (DA) levels. Both AII and AII receptors as well as angiotensinogen and angiotensin-converting enzyme (ACE) have been observed in the striatum (Quinlan and Phillips, 1981;Brownfield et al, 1982;Chai et al, 1987;Allen et al, 1992Allen et al, , 1998, and AII stimulates the release of newly synthesized DA via angiotensin type 1 receptors (AT 1 ) located in the striatal DA terminals (Mendelsohn et al, 1993;Brown et al, 1996;Ge and Barnes 1996).…”
mentioning
confidence: 99%